Global trends in research of high-throughput sequencing technology associated with chronic wounds from 2002 to 2022: A bibliometric and visualized study - Meng, Hao; Peng, Yu; Li, Pinxue; Su, Jianlong; Jiang, Yufeng; Fu, Xiaobing (Frontiers in Surgery, 2023)
Chronic wounds are a complex medical problem. With the difficulty of skin healing, the microbial ecology of chronic wounds is an essential factor affecting wound healing. High-throughput sequencing (HTS) technology is a vital method to reveal the microbiome diversity and population structure of chronic wounds. This bibliometric and visualization study was applied to delineate the scientific output characteristics, research trends, hotspots and frontiers of HTS technologies related to chronic wounds globally over the past 20 years. We searched the Web of Science Core Collection (WoSCC) database for articles published between 2002 and 2022 and their full record information. The Bibliometrix software package was used to analyze bibliometric indicators and VOSviewer visualization analysis results. This study reveals trends and hot spots about HTS associated with chronic wounds. A total of 449 original articles were reviewed, and the results showed that the number of annual publications (Np) about HTS associated with chronic wounds has steadily increased over the last 20 years. The USA and China produce the most articles and have the highest H-index, while the USA and England have the largest number of citations (Nc) in this field. The University of California, Wound Repair and Regeneration and National Institutes of Health Nih USA were the most published institutions, journals and fund resources, respectively. The global research could be divided into 3 clusters as follows: microbial infection of chronic wounds, the healing process of wounds and microscopic processes, skin repair mechanism stimulated by antimicrobial peptides and oxidative stress. In recent years, "wound healing", "infections", "expression", "inflammation", "chronic wounds", "identification" and "bacteria" “angiogenesis", "biofilms" and "diabetes" were the most frequently used keywords. In addition, research on "prevalence", "gene expression", "inflammation" and "infection" has recently become a hotspot. The USA and China were the largest contributors in this field. Future research efforts in this field should include the following aspects: HTS technology to assist in identifying the microbial ecology of chronic wounds, analysis of the microbiota of diabetic foot wounds, and search for targets to promote the healing of chronic wounds.